2014
DOI: 10.7567/jjap.54.011502
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mg loading on the high-frequency tunability of Ba0.8Sr0.2TiO3ceramics

Abstract: The effect of Mg loading on the high-frequency tunable properties and dielectric loss of Ba 0.8 Sr 0.2 Ti 1%x Mg x O 3 (BSTM) ceramics was investigated. Variation in the lattice parameters and the 90°domain configuration with Mg loading indicated a decrease in the tetragonal distortion. Additionally, the 90°domain size decreased slightly with a low Mg loading, up to 0.1 mol %, resulting in a higher domain-wall density compared with the nondoped specimen. The 0.075 mol % Mg-loaded BSTM ceramic exhibited the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Barium strontium titanate (Ba 1− x Sr x TiO 3 ; BST) is a well‐known tunable ferroelectric that has a large nonlinear dielectric response under an electric dc field. We have reported the polarization contribution to the overall tunability of the normal ferroelectric Ba 0.8 Sr 0.2 TiO 3 (0.8‐BST) that has ferroelectric domains at room temperature . The dipole polarization in normal ferroelectrics is derived from the dipole fluctuation in the 90° domain walls; the dipole polarization significantly contributes to the permittivity in normal ferroelectrics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barium strontium titanate (Ba 1− x Sr x TiO 3 ; BST) is a well‐known tunable ferroelectric that has a large nonlinear dielectric response under an electric dc field. We have reported the polarization contribution to the overall tunability of the normal ferroelectric Ba 0.8 Sr 0.2 TiO 3 (0.8‐BST) that has ferroelectric domains at room temperature . The dipole polarization in normal ferroelectrics is derived from the dipole fluctuation in the 90° domain walls; the dipole polarization significantly contributes to the permittivity in normal ferroelectrics.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported the polarization contribution to the overall tunability of the normal ferroelectric Ba 0.8 Sr 0.2 TiO 3 (0.8-BST) that has ferroelectric domains at room temperature. 11,12 The dipole polarization in normal ferroelectrics is derived from the dipole fluctuation in the 90°domain walls; the dipole polarization significantly contributes to the permittivity in normal ferroelectrics. The 90°domain size strongly affects the tunability and the dielectric constant; smaller domains improve tunability because of the larger density of the domain wall vibration.…”
mentioning
confidence: 99%
“…The introduced VTi were each compensated for by the formation of two VnormalO (i.e., 2 mol% of oxygen vacancies for A/B = 1.01 BST to compensate the 1 mol% of Ti deficiencies). By comparison, samples loaded with 0.5 mol% of Mg (with each Mg being compensated for by one VnormalO, leading to ~0.5 mol% of oxygen vacancies) showed that most of the ferroelectric domains vanished, accompanied by a marked reduction in the T m from 70°C to ˜ 40°C for the Mg‐BST system . However, this was not observed for the Ti‐deficient systems.…”
Section: Resultsmentioning
confidence: 96%
“…BSTs with x = 0.8‐1.0 possess 90° domains due to the nature of the present dipole polarization, i.e., flat temperature dependence of permittivity near room temperature due to the higher T m (70°C‐130°C) . We have previously reported this domain configuration effect on the resulting microwave tunability properties for polycrystalline Ba 0.8 Sr 0.2 TiO 3 (0.8 BST) . The microwave tunability of 0.8 BST ceramics was significantly enhanced by decreasing the 90° domain width.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation